Enhancing the performance of TEG system coupled with PCMs by regulating the interfacial thermal conduction. (November 2020) - Liu, Anbang; Zou, Jiapu; Wu, Zihua; Wang, Yuanyuan; Tian, Yuanyuan; Xie, Huaqing
Abstract: Heat storage with phase change materials (PCMs) is promising to enhance the performance of thermoelectric generator (TEG) systems. Optimizing the thermal management in practical application is crucial to improve the performance of these TEG-PCM coupling systems. In this study, a TEG system coupled with PCMs has been fabricated and thermal interface materials (TIMs) with different thermal conductivities were used to regulate the interfacial thermal conduction between heat storage unit, TEG and heat exchanger. The experimental results revealed that the interfacial thermal conduction has substantial effects on the temperatures and performance of the TEG system coupled with PCMs. With the improvement of the interfacial thermal conduction, the time of the temperature of PCMs maintaining stable during cooling ( t p ) was shortened, while the average of output power of TEG system within this period ( P p ) was increased. It indicates that the excess energy generated with the coupled PCMs would not increase monotonously with the enhancement of interfacial thermal conduction. We proposed a method to explore the optimal interfacial thermal conduction for the largest excess energy by performing polynomial fitting analysis of t p and P p, respectively. This study provided a feasible means to improve the performance of TEG-PCM coupling systems by regulating the interfacial thermal conduction. Highlights: A TEG system coupled with eutectic alloy PCMs of Ag-ln-Sn is proposed. Three types of TIMs were used to optimize thermal management in the experiment. A method to explore the optimal interfacial thermal conduction was suggested. Electrical energy is significantly enhanced when using the appropriate TIM.